RESTRUCTURATION OF QUECHUA WORDS IN SPANISH: A MORPHOLOGICAL DESCRIPTION - Galvez Astorayme, Isabel (2012)
Spanish contains a group of words derived from Quechua which have, in fact been restructured by the morpho-phonological patterns of Spanish. This production, quite evident from the linguistic contact of Spanish and Quechua has increased Spanish vocabulary with the new lexical contribution of Quechua. We present here the changes that Quechua words have gone through when incorporated into Spanish in a systematic manner. Specifically this is a synchromatic description of the phonological and morphological phenomena which may be seen in the words recorded in the Dictionary of the Spanish Language (DRAE, [twenty second edition]).